Effect of anti-pilus antibodies on survival of gonococci within guinea pig subcutaneous chambers. - Lambden, P R (1982)
Guinea pigs were immunized with either alpha or beta pili from Neisseria gonorrhoeae P9 before the inoculation of subcutaneous chambers with a mixture of variants having alpha, beta, gamma, or delta pili. Animals immunized with alpha pili showed significant protection, but those immunized with beta pili did not. The degree of protection could be correlated with the cross-reactivity of the antibodies produced to the heterologous pilus types.